Pengembangan Suplemen Bahan Ajar Berbasis Kearifan Lokal Kota Singkawang pada Materi Bahasa Indonesia Kelas IV - Eriviana Putri; Siti Halidjah; Suparjan Suparjan (PALAPA, 2022)
This study aims to develop teaching material supplement products based on local wisdom of Singkawang City for grade IV elementary school that is feasible to be used in assisting thematic learning activities with the theme of 8 sub-themes 1. The method used in this study is a research method and development by adapting the ADDIE model. Source of this research data are 27 students of class IV Elementary School 82 Singkawang. Data collection techniques in this study were interviews and observation. The results showed that the development of teaching materials based on The local wisdom of Singkawang City has gone through five research steps; analysis, design, development, implementation, and evaluation. Product validity teaching material supplements obtained a very good category with an average percentage value an average of 92.5% in the language aspect, 91% in the design aspect, and 91.5% in the Theory.